Dynamic instability analysis of sandwich plates with CNT reinforced facesheets. (20th June 2016) - Sankar, A.; Natarajan, S.; Ganapathi, M.
Abstract: In this paper, the dynamic instability characteristics of sandwich panels with carbon nanotube (CNT) reinforced facesheets subjected to in-plane periodic load is investigated using a shear flexible QUAD-8 serendipity element. The formulation accounts for the realistic variation of the displacements through the thickness, possible discontinuity in slope at the interface and the thickness stretch affecting the transverse deflection. The influence of the aerodynamic force due to airflow over the plate, the in-plane and the rotary inertia effects are also included in the formulation. The accuracy of the present formulation is demonstrated considering the problems for which solutions are available. A detailed numerical study is carried out to bring out the efficacy of the present higher-order plate theory over the first-order plate theory. The present study examines the influence of the volume fraction of the CNT, core-to-facesheet thickness, the plate thickness and aspect ratio, damping and temperature on the dynamic instability boundaries and its associated origin of instability forcing frequencies. The effect of airflow over such sandwich plate is also investigated. The boundaries of the principal instability region are represented in the non-dimensional excitation frequency-load amplitude plane.